2013
DOI: 10.1016/j.wasman.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Managing compost stability and amendment to soil to enhance soil heating during soil solarization

Abstract: Soil solarization is a method of soil heating used to eradicate plant pathogens and weeds that involves passive solar heating of moist soil mulched (covered) with clear plastic tarp. Various types of organic matter may be incorporated into soil prior to solarization to increase biocidal activity of the treatment process. Microbial activity associated with the decomposition of soil organic matter may increase temperatures during solarization, potentially enhancing solarization efficacy. However, the level of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 21 publications
3
54
2
1
Order By: Relevance
“…Opportunistic species of nematodes and microbes quickly re-colonize after treatment and many of these groups are antagonistic to pests (Gamliel and Stapleton 1993;Mazzola et al 2012;Simmons et al 2014;Stapleton 2000), resulting in very different microbial communities than those found in either fumigated or nonfumigated soil (Drenovsky et al 2005;Shennan et al 2013). For ASD, steam and solarization, researchers continue to explore using different amendments (e.g., rice bran, brassica seed meal) to enhance pest control and optimize the carbon sources used to control specific pathogens (Fennimore et al 2014;Shennan et al 2013;Shennan et al 2014;Simmons et al 2013). …”
Section: Soil Solarization Steam and Asdmentioning
confidence: 99%
“…Opportunistic species of nematodes and microbes quickly re-colonize after treatment and many of these groups are antagonistic to pests (Gamliel and Stapleton 1993;Mazzola et al 2012;Simmons et al 2014;Stapleton 2000), resulting in very different microbial communities than those found in either fumigated or nonfumigated soil (Drenovsky et al 2005;Shennan et al 2013). For ASD, steam and solarization, researchers continue to explore using different amendments (e.g., rice bran, brassica seed meal) to enhance pest control and optimize the carbon sources used to control specific pathogens (Fennimore et al 2014;Shennan et al 2013;Shennan et al 2014;Simmons et al 2013). …”
Section: Soil Solarization Steam and Asdmentioning
confidence: 99%
“…First, the additional microbiota and nutrient source associated with the amendment can enhance soil heating through biological heating. For example, amending soil with compost and organic matter yielded temperature increases between 2 and 5ºC greater than nonamended soil when both were solar heated (Achmon et al, 2015;Simmons et al, 2013;Simmons et al, 2016). Secondly, anaerobic microbial fermentation of organic matter can result in the production of organic compounds such as volatile fatty acids (VFAs) that accumulate due to the physical barrier of the plastic tarp.…”
Section: Soil Biosolarization (Sbs) Can Be a Sustainable Soil Pest Comentioning
confidence: 99%
“…Like compost, which has been shown to be an effective inoculum for biosolarization (Simmons et al, 2013), digestates contain robust, anaerobic, organic matter-degrading microbial communities that may also tolerate biosolarization. Studies have shown that SBS can increase the proportion of facultative and obligate anaerobic microorganisms in the soil (Yao et al, 2016).…”
Section: Soil Biosolarization (Sbs) Can Be a Sustainable Soil Pest Comentioning
confidence: 99%
See 1 more Smart Citation
“…The pesticidal efficacy of solarization is often complemented by amendment with organic matter (Stapleton 2000;Schönfeld et al 2003;Simmons et al 2013). The effectiveness of soil solarization against many pathogens, weeds and soil arthropods in the cultivation of various crops has been well demonstrated in both open fields and greenhouses (Stapleton 2000).…”
Section: Introductionmentioning
confidence: 99%